2022
DOI: 10.1111/1749-4877.12616
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics provides insights into the evolution and adaptation of tree shrews (Tupaia belangeri) in China

Abstract: Physiological adaptation of tree shrews (Tupaia belangeri) to changing environmental temperature has been reported in detail. However, the T. belangeri origin (mainland or island), population history, and adaptation to historical climate change remain largely unknown or controversial. Here, for the first time, we sequenced the simplified genome of 134 T. belangeri individuals from 12 populations in China and further resequenced one individual from each population. Using population genomic approaches, we first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…2016; Ren et al. 2023). Conservation genomics greatly expands the traditional scope of conservation genetics, which helps decision‐makers create more effective strategies for species conservation.…”
Section: Conservation Genomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…2016; Ren et al. 2023). Conservation genomics greatly expands the traditional scope of conservation genetics, which helps decision‐makers create more effective strategies for species conservation.…”
Section: Conservation Genomicsmentioning
confidence: 99%
“…In the context of endangered species, data pertaining to genomic variation can be used to address critical questions that are relevant to protecting endangered species. More specifically, genomic variation can help researchers better understand diversity patterns and estimate effective population sizes, migration rates, gene flow, inbreeding, and the prevalence of harmful mutations (Allendorf et al 2010;Khan et al 2016;Ren et al 2023). Conservation genomics greatly expands the traditional scope of conservation genetics, which helps decisionmakers create more effective strategies for species conservation.…”
Section: Conservation Genomicsmentioning
confidence: 99%
“…Using EIGENSOFT 3.0 software, principal component analysis (PCA) was carried out (Patterson et al, 2006). The neighbor-joining (NJ) approach in MAGA 7.0.26 was employed to reconstruct phylogenetic trees of 161 individuals (Koichiro et al, 2011;Ren et al, 2022).…”
Section: Population Structurementioning
confidence: 99%
“…The complex and ever-changing natural environment may lead to genetic and phenotypic variations in the T. belangeri. The research results of genomics and metabolomics have found that distinct genetic and metabolic differentiation has occurred in T. belangeri in different regions (Ren et al, 2023;Hou et al, 2023). Studies on some morphological indicators have also found that there were certain variations in body index, fullness, body composition, digestive tract and skull morphology of T. belangeri in different regions, which may be related to distribution, altitude and geographical barriers (Gao et al, 2017;Ren et al, 2019b;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%